Chemometric study to discover dual-functional food spoilage inhibitors from Polygonum minus extract - Ahmad, Mohammad Norazmi; Abdullah, Erna Normaya (UKM Publisher, 2021)
Nowadays, there are approximately 470 million small-to-medium enterprises (SMEs) and farmers across developing countries losing income (average 15%) due to food spoilage (Rockefeller Foundation 2013). It has been estimated that more than 25% of the world's food spoilage belongs to biological or microbial spoilage (Nychas & Panagou 2011). Every year, microbial spoilage contributes a significant impact on the food's quality and shelf life during the storage and distribution processes. Understanding the mechanism of microbial spoilage that occurred is a vital part of designing or exploring an alternative microbial inhibitor from natural sources. Natural antimicrobials could be an effective way to prevent or minimise food spoilage and foodborne outbreaks as an alternative to chemical preservatives. Microbial agents are commonly incorporated in food products to retard the growth of pathogenic microorganisms such as bacterial and fungi. They can be either be chemically synthesised or extracted naturally from plant origins (Meira et al. 2017). In Malaysia, kesum (Polygonum minus) is rich in phytochemical compounds such as flavonoids, suggesting an association with medicinal properties that can be used as an alternative plant-derived food additive (microbial spoilage inhibitor). In this chapter, the chemometric techniques (Adeniji et al. 2020), namely, hierarchical clustering (HCA) and principal component analysis (PCA), have been used to cluster and classify the phytochemical compounds of Polygonum minus into the same groups with the control of microbial spoilage, namely streptomycin (bacterial inhibitor) and nystatin (fungal inhibitor) (FDA 2019).